Rad9/53BP1 promotes DNA repair via crossover recombination by limiting the Sgs1 and Mph1 helicases - Matteo Ferrari (Nature Portfolio, 2020)
In budding yeast, the 53BP1 ortholog Rad9 limits the resection nucleolytic processing of DNA double strand breaks. Here the authors reveal that Rad9 promotes long tract gene conversions, BIR and CO, during the HR repair of a DSB via modulation of Sgs1 and Mph1 helicases.